Effectiveness of Providing Local PMT and Milk on Weight Gain in Pregnant Women With Chronic Energy Deficiency Syndrome (CED) or KEK in The Working Area of UPTD Kalapanunggal Public Health Center - Santi Mala; Lisa Trina Arlym; Rukmaini (International Journal of Midwifery and Health Sciences, 2025)
ABSTRACT   Introduction: Chronic Energy Deficiency Syndrome (CED) in pregnant women can cause various health problems for the pregnant woman herself and the fetus. Factors causing CED in pregnant women include family income, parity, age, diet, maternal knowledge, and infection. However, research on its effectiveness in the Kalapanunggal Community Health Center working area is still limited. Objective: To determine the effect of PMT administration on weight gain in pregnant women with CED in the Kalapanunggal Community Health Center working area. Method: This type of research is a quantitative study with a quasi-experimental method with one group pretest posttest. The sample in this study was all pregnant women who experienced CED at the Kalapanunggal Community Health Center, totaling 30 people. The sampling technique in this study used a purposive sampling technique. The instruments in this study were observation sheets for weight gain. Results: The results of the study showed that the average weight of pregnant women before receiving PMT can be seen that there was an increase in the average weight of pregnant women between before being given PMT (46.827±4.5343) and after being given PMT Recovery for 3 months (49.013±4.5583). Conclusion: There is an effect of providing additional food (PMT) in the form of Local PMT on weight gain of pregnant women at the Kalapanunggal Health Center, Sukabumi Regency.